Implementasi QRIS sebagai Media Pembayaran Elektronik bagi UMKM di Porch Café - Safitri, Rama; Suvia, Tiwi; Arafat, Mahfuzan; Shandika, Muhammad; Trianingsih, Ayu Retno; Pramadeka, Katra (Economic Reviews Journal, 2025)
This study aims to analyze the implementation of QRIS (Quick Response Code Indonesian Standard) as an electronic payment media in MSMEs, especially at Porch Cafe. In the current era of digitalization, non-cash payment methods are increasingly in demand by the public because they are considered more practical, efficient, and safe. Porch Cafe as one of the MSME actors has adopted the QRIS system in its transaction activities to increase customer convenience and operational efficiency. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the implementation of QRIS has a positive impact on increasing non-cash transactions, speeding up the payment process, and improving the image of business professionalism. However, there are still challenges such as limited customer digital literacy and dependence on the internet network. Therefore, education strategies and strengthening digital infrastructure are needed to support the optimal utilization of QRIS by MSMEs.